Anticonjugation and Antibiofilm Evaluation of Probiotic Strains Lactobacillus plantarum 22F, 25F, and Pediococcus acidilactici 72N Against Escherichia coli Harboring mcr-1 Gene - Apiwatsiri, Prasert; Pupa, Pawiya; Yindee, Jitrapa; Niyomtham, Waree; Sirichokchatchawan, Wandee; Lugsomya, Kittitat; Shah, Asad Ali; Prapasarakul, Nuvee (Frontiers in Veterinary Science, 2021)
Several species of lactic acid bacteria (LAB) are commonly used as probiotics and as an alternative to antibiotics in various industries, especially in the livestock industry. This study aimed to investigate the anti-conjugation and anti-biofilm activity of cell-free supernatant (CFS) of Thai LAB strains (Lactobacillus plantarum 22F, 25F, and Pediococcus acidilactici 72N) against colistin-resistant E. coli isolates. A total of 6 colistin-resistant E. coli strains were isolated from different sources, including pigs, farmers, and farmhouse environments. The E. coli were characterized by plasmid profiling, PCR detection of mcr-1 gene, and antibiotic susceptibility patterns. The CFS at the dilutions ≥1:16 was chosen as the proper dilution for anti-conjugation assay. Besides, it could significantly reduce the transfer frequencies of resistance gene mcr-1 up to 100 times compared to the neutralizing CFS (pH 6.5). The biofilm production in the planktonic stage was reduced by non-neutralizing and neutralizing CFS determining with crystal violet staining assay up to 82% and 60%, respectively. Moreover, the non-neutralizing CFS also inhibited the biofilm formation in the sessile stage up to 52%. The biofilm illustration was confirmed by scanning electron microscopic (SEM). These results agreed with the findings of the crystal violet technique, which showed a significant reduction in the cell density, aggregation, and extracellular polysaccharide (EPS) matrix. The application of Thai LAB may serve as an attractive alternative to antibiotics for reducing biofilm formation and limiting the proliferation of antibiotic-resistant genes.